2000
DOI: 10.1164/ajrccm.162.3.9905104
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Normal Lung Sounds, Age, and Gender

Abstract: Auscultation is one of the most important noninvasive and feasible methods for the detection of lung diseases. Systematic changes in breathing sounds with increasing age are of diagnostic importance. To investigate these changes, we recorded lung sounds taken from four locations in the posterior thorax of 162 subjects, together with airflow. The data were analyzed according to age, sex, and smoking habit. In order to describe the power spectrum of the lung sounds, we calculated mean and median frequency, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 31 publications
7
46
0
3
Order By: Relevance
“…The female snorers of this study were observed to have higher frequency-based features ( p f and 2 mp f ) (p < 0.05) and lower energy feature (p < 0.05) than the male snorers. Although there was no study investigating the gender effect on the snoring sounds, this observation is congruent with findings reported in two studies focused on breath and lung sounds [33,34]. According to those studies, breath and lung sounds in healthy women contain higher frequency components than in men.…”
Section: Resultssupporting
confidence: 85%
“…The female snorers of this study were observed to have higher frequency-based features ( p f and 2 mp f ) (p < 0.05) and lower energy feature (p < 0.05) than the male snorers. Although there was no study investigating the gender effect on the snoring sounds, this observation is congruent with findings reported in two studies focused on breath and lung sounds [33,34]. According to those studies, breath and lung sounds in healthy women contain higher frequency components than in men.…”
Section: Resultssupporting
confidence: 85%
“…Numerous studies have explored the use of breath sounds to develop a ''pulmonary hearing aid'' for diagnosing different respiratory diseases [17][18][19][20], based on recorded breath sounds in normal condition and various diseases [17][18][19][20]. The method described herein does not use a databank.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, new evidence 23 gathered by Gavriely et al, (1995) [11] and Gross et al, (2000) [12] indicates no differences 24 Volunteers willing to participate contacted the researchers. In this first contact, researchers 1 provided detailed explanations about the study, verified participants' eligibility and scheduled 2 an appointment to perform data collection.…”
Section: Introductionmentioning
confidence: 99%